Characteristics of four-limb blood pressure and brachial-ankle pulse wave velocity in Chinese patients with Takayasu arteritis. (31st December 2022) - Chen, Yang; Dong, Hui; Li, Hong-Wu; Zou, Yu-Bao; Jiang, Xiong-Jing
Abstract: Purpose: Takayasu arteritis (TA) is a rare disease, which is frequently misdiagnosed or its diagnosis can be missed. This study aimed to analyse the characteristics of four-limb blood pressure (4LBP) and brachial-ankle pulse wave velocity (baPWV) in patients with TA, which could be useful in disease detection. Materials and Methods: We consecutively enrolled 182 patients with TA at Fuwai Hospital between January 2013 and January 2016. Pulse pressure (PP), pulsatile index (PI), inter-arm systolic blood pressure (SBP) difference (IASBPD), inter-leg SBP difference (ILSBPD), ankle–brachial index (ABI), baPWV, and inter-side baPWV difference (ΔbaPWV) were analysed and compared with those of age-, sex-, and SBP-matched participants without cardiovascular diseases. Results: In the TA group, the diastolic blood pressure was lower (67.4 ± 23.7 vs 84.1 ± 15.0 mmHg), PP was larger (69.7 ± 23.6 vs 53.7 ± 10.6 mmHg), PI was higher (1.3 ± 2.1 vs. 0.6 ± 0.1 mmHg), IASBPD was larger (18.2 ± 24.1 vs 4.2 ± 3.3 mmHg), and ILSBPD was larger (10.7 ± 15.0 vs 5.3 ± 4.1 mmHg) than those of the controls (all p  < 0.01). Moreover, the proportions of PP >70 mmHg (36.8% vs 4.4%), PI > 1.0 (40.1% vs 2.2%), IASBPD >15 mmHg (34.6% vs. 0%), highest ABI >1.4 (17.6% vs. 0%), ILSBPD >15 mmHg (14.8% vs. 3.3%), lowest ABI < 0.9 (24.7% vs 2.2%), and ΔbaPWV > 185 cm/s (28.6% vs. 1.1%) were significantly greater in the TA group than in the control group (all p  < 0.01). Approximately 80.8% of patients with TA (vs. 10.4% of controls) presented with at least one of these seven parameters ( p  = 0.000). Conclusion: The characteristics of 4LBP and baPWV in most patients with TA were abnormal, which helped us perform non-invasive primary screening and comprehensive evaluation of vascular lesions in such patients. PLAIN LANGUAGE SUMMARY: In daily life, many people measure the blood pressure of the arm but measuring the blood pressure of a single arm is inadequate because some hypertension and vascular diseases cannot be detected this way. Synchronous limb blood pressure measurements may be used to close this gap. Measuring synchronous limb blood pressure is very convenient and helps patients understand the value of limb blood pressure and examine many other useful parameters, such as the blood pressure differences between the two arms and two legs, as well as the ankle arm index. These values and derived parameters can also help detect many vascular diseases. Takayasu arteritis is a rare disease in young women. However, the aorta and branches of these patients are narrow or occluded. Patients often experience vague and ambiguous symptoms, such as hypertension or dizziness, so they are likely to be overlooked or misdiagnosed. Our study summarises the results of synchronous limb blood pressure measurements in patients with Takayasu arteritis and compares their results with those of a control population. Synchronous limb blood pressure measurements are easy and convenient and can detect vascular problems, which may improve the ability to diagnose Takayasu arteritis.